2004
DOI: 10.2307/4090472
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Introgression between Golden-Winged Warblers (Vermivora chrysoptera) and Blue-Winged Warblers (V. pinus) in Eastern North America

Abstract: ABSTRACT.• Golden-winged Warblers (Vermivora chrysoptera) and Blue-winged Warblers (V: pinus) are small, brightly colored Neotropical migrant birds that breed in eastern North America. Wherever the two species occur together, they hybridize to a limited degree, producing distinctive hybrid phenotypes. In recent decades, chrysoptera has experienced dramatic population declines across much of its range. Those declines have often been correlated with establishment and increase of pinus in the same areas, but it r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…A more comprehensive recent survey (Shapiro et al 2004) examined phenotype-haplotype associations in a greatly expanded sample of individual warblers from additional study populations. In contrast to the rapid and unidirectional introgression seen at Gill's sites, Shapiro et al (2004) found bi-directional introgression at all locations where both species were well represented, with no tendency for disproportionate introgression as indicated by Blue-winged haplotypes in Goldenwinged phenotype individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A more comprehensive recent survey (Shapiro et al 2004) examined phenotype-haplotype associations in a greatly expanded sample of individual warblers from additional study populations. In contrast to the rapid and unidirectional introgression seen at Gill's sites, Shapiro et al (2004) found bi-directional introgression at all locations where both species were well represented, with no tendency for disproportionate introgression as indicated by Blue-winged haplotypes in Goldenwinged phenotype individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research related to the decline of the Golden-winged Warbler has focused on hybridization with the Blue-winged Warbler (Gill 1997, Shapiro et al 2004, Dabrowski et al 2005. Although understanding the genetic challenges that face the species is important, improving habitat conditions for the Goldenwinged Warbler in newly colonized areas such as those found in eastern Kentucky is also valuable, particularly where the Blue-winged Warbler is absent.…”
Section: Introductionmentioning
confidence: 99%
“…The breakdown of reproductive barriers and subsequent hybridization between GWWA and BWWA populations is well documented (Shapiro et al 2004, Dabrowski et al 2005, Vallender et al 2009) and is considered a threat to many GWWA populations (Parkes 1951, Gill 1980, Buehler et al 2007. We provide evidence fire may be creating conditions leading to habitat partitioning and isolation of GWWA and BWWA populations in central Wisconsin.…”
Section: Discussionmentioning
confidence: 88%
“…Hybridization between the two species has received extensive phenotypic (Parkes 1951, Gill 1980, 1987, mitochondrial DNA (mtDNA) (Gill 1997, Shapiro et al 2004, Dabrowski et al 2005, and nuclear DNA ) study indicating genetic introgression is bi-directional (Shapiro et al 2004, Dabrowski et al 2005) and extensive (Vallender et al 2009). Based on the mtDNA studies, the species' genomes overlap by 95.1-97.0% (Gill 1997, Shapiro et al 2004, Dabrowski et al 2005 and split from an ancestral species approximately 1.5 million years before present (Gill 2004). Based on genetic similarity and time since separation, relatively easy genetic exchange between the sister species is predictable (Price and Bouvier 2002).…”
Section: Introductionmentioning
confidence: 99%